STRATEGI PEMBIASAAN SHALAT BERJAMA’AH PADA SISWA DI MI MA’ARIF NU 01 PASIR KULON KECAMATAN KARANG LEWAS KABUPATEN BANYUMAS - Umiyati; Umiyati (Pusat Studi Pendidikan dan Kreativitas Guru, 2018)
The background of congregation prayer habituation strategy in the students originated from the existence of internal school activities in which students perform the habit of duhur prayer in congregation. However, in its implementation does not always run according to the school procedure because the place to do the congregation prayer has not existed and there is no clear assertiveness from the school related to the implementation of congregation prayer to be implemented. And there is no strategy in the implementation of congregation prayer. This study aims to provide an overview of the strategy of congregation prayer in students at MI Ma’arif NU 01 Pasir Kulon. This study type research is using field research that is descriptive qualitative that the authors do direct research in the field to obtain data or information directly by visiting the location of respondents. Data collecting techniques were conducted using observation, interview, questionnaire, documentation and combined techniques. The purpose of this type of research is descriptive research because it is intended to analyze and present the actual situation occurred in the location of research on the habit of congregation prayer in MI Ma’arif NU 01 Pasir Kulon. As a result of this research is strategy of habitual congregation prayer to students at MI Ma’arif NU 01 Pasir Kulon is: The existence of praying duhur prayer in continuously, principal, teachers and employees overseeing activities of praying duhur congregation has been scheduled, routine oral suggestion at the ceremony and additional hours of special religious lessons, direct control to the classes and around the school building for students who do not pray, and give warning to students who not do congregation prayer in congregation. And the existence of several supporting factors and inhibiting factors in the process of implementation of congregation prayer.